OS03.3.A Characterization of long-term metabolic changes of irradiated brain metastases using serial dynamic FET PET imaging. (9th September 2021) - Galldiks, N; Stoffels, G; Werner, J; Bauer, E K; Baues, C; Celik, E; Ruge, M I; Fink, G R; Langen, K; Lohmann, P
Abstract: BACKGROUND: In the present study, we characterized the long-term metabolic changes of brain metastases irradiated with stereotactic radiosurgery (SRS) by sequential dynamic PET imaging using the radiolabeled amino acid O-(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET). We hypothesized that this approach is of considerable clinical value to diagnose delayed radiation-induced changes. MATERIAL AND METHODS: From 2010–2021, we retrospectively identified patients with brain metastases from solid extracranial primary tumors who (i) were treated with SRS with or without concurrent immunotherapy using checkpoint inhibitors, (ii) had equivocal or progressive MRI findings after SRS, and (iii) subsequently underwent at least two additional dynamic FET PET scans during follow-up for long-term evaluation. Mean tumor-to-brain ratios (TBR) and the dynamic FET PET parameter time-to-peak were obtained. Diagnostic performances were calculated using receiver operating characteristic curve analyses. Diagnoses were confirmed histologically or clinicoradiologically. RESULTS: We identified 36 patients with 98 FET PET scans (median number, 3; range, 2–6). Concurrent to SRS, 8 patients (22%) were treated with checkpoint inhibitors. Following SRS, suspicious MRI findings occurred after a median time of 11 months (range, 2–64 months). Subsequently, FET PET scans were acquired over a median period of 13 months (range, 5–60 months). The overall median follow-up time was 26 months (range, 8–101 months). Twenty-one patients (58%) had delayed radiation-induced changes. TBRs calculated from the last available FET PET scan showed the highest accuracy (92%) to identify delayed radiation-induced changes (threshold, 1.95; P <0.001). CONCLUSION: FET PET has a high diagnostic accuracy for characterizing the long-term changes of irradiated brain metastases.